STUDY OF THE OPERATION OF SOME MEDICAL DEVICES AND THEIR PHYSICAL APPLICATIONS. A FIELD STUDY ON THE ULTRASOUND DEVICE - Dieary Ali Mohammed; Sara rafeeq saeed; Khawla Akram Ahmed (Journal of Medical Genetics and Clinical Biology, 2024)
One of the most important branches of applied physics is the application of physics in the medical field, especially in the diagnosis and treatment of human diseases. It is divided into four main branches: (radiation therapy, nuclear medicine, diagnostic imaging, and radiation protection). The Radiation Therapy Physics Division is often the largest, as physicists provide support services to the Department of Radiation Oncology, ensuring that it accurately reaches a patient in the hospital, such as planning radiation doses and X-rays. Classification and MRI oncology. Diagnostic imaging devices such as Important Humans and their treatment. We will also discuss some other medical devices (the EKG device, the EEG device, and the centrifuge). Physics in medicine is of great importance because it is manifested in employing various physical phenomena and making the most of them with devices that allow us to diagnose and treat many diseases, and we see now with the development of these, The devices have become an important possibility in wave therapy without the need to resort to surgical operations